STUDENTS PERCEPTION IN USING CHAT-GPT TECHNOLOGY TOWARD LEARNING ACTIVITIES - Nagata Zamzami; Erwin Hari Kurniawan; Wildan Isna Asyhar (JURNAL EDUCATION AND DEVELOPMENT, 2024)
The aim of this study is to know the benefits and students' perceptions of using Chat-GPT Technology toward learning activities. It is to describe the students’ perception of using Chat-GPT technology toward learning activities in class with the lecturer. The data was collected through a questionnaire and interview. Furthermore, the subject in this research was students in the Language Education Study Program in Teacher Training and Education Faculty in Universitas Islamic of Kadiri, academic year 2023/2024. The respondents were 40 students of English language education FKIP UNISKA-Kediri. Collecting data from interviews and questionnaires served as the first step in the data analysis process. According to the research findings, students expressed satisfaction with Chat-GPT's speed and accuracy of responses, ease of use, benefits, and improvement of knowledge. They also expressed satisfaction with Chat-GPT's ability to increase efficiency and effectiveness of time and improve learning activities. A few students even felt inspired to write scientific papers using the ideas they received from Chat-GPT. On the other hand, students felt there were concerns about unfair selection and the risk of plagiarism that could undermine critical thinking skills. Given the positive perception given by students about the use of Chat-GPT in learning, regulations on using Chat-GPT should be given to teachers before allowing students to use Chat-GPT so that student controls and restrictions in using Chat-GPT are not excessive so that learning activities can run orderly, fairly and responsibly.